Impact of biochar and root-induced changes on metal dynamics in the rhizosphere of Agrostis capillaris and Lupinus albus - Houben, David; Sonnet, Philippe (Chemosphere (Oxford), 2015)
•Biochar application has a liming effect in bulk soil.•Adding biochar shift metals from exchangeable pool to carbonate-bound pool in bulk soil.•Root-induced acidification counteracts the liming effect of biochar in rhizosphere.•Metals shifted to carbonate-bound pool were re-mobilized in rhizosphere.•Limiting rhizosphere acidification is suggested to optimize the effects of biochar. Rhizosphere interactions are deemed to play a key role in the success of phytoremediation technologies. Here, the effects of biochar and root-induced changes in the rhizosphere of Agrostis capillaris L. and Lupinus albus L. on metal (Cd, Pb and Zn) dynamics were investigated using a biotest on a 2mm soil layer and a sequential extraction procedure (Tessier’s scheme). In the bulk soil, the application of 5% biochar significantly reduced the exchangeable pool of metals primarily due to a liming effect which subsequently promoted the metal shift into the carbonate-bound pool. However, metals were re-mobilized in the rhizosphere of both A. capillaris and L. albus due to root-induced acidification which counteracted the liming effect of biochar. As a result, the concentrations of metals in roots and shoots of both plants were not significantly reduced by the application of biochar. Although the study should be considered a worst-case scenario because experimental conditions induced the intensification of rhizosphere processes, the results highlight that changes in rhizosphere pH can impact the effectiveness of biochar to immobilize metals in soil. Biochar has thus a potential as amendment for reducing metal uptake by plants, provided the acidification of the rhizosphere is minimized.